Effect of Temperature on in vitro Survival of some Bradyrhizobium Strains - N. Babiker, Nazar; M. Babiker, Hashim; O. Mukhtar, Nuri (Gezira Journal of Agricultural Science; Vol 3 No 1 (2005), 2021)
Evaluating Rhizobium survival in inoculants exposed to high temperature may be considered the first stage in identifying potential inoculant strains that would withstand temperature stress on inoculated seeds in the field. High temperatures may adversely affect the survival of Rhizobium in packaged inoculants during storage and inoculation (Somasegaran et al ., 1984), and the viability of rhizobia in inoculants may be lost in a few weeks at temperatures of 350C or higher (Smith, 1987). Low storage temperature, however, is not always better than room temperature, as some slow growing bradyrhizobia were found to survive better at 260C than at 40C (Vincent, 1982). Soil temperature is also an important environmental variable that affects general biological activity. Nodulation and N 2 -fixation were observed under a wide range of temperatures with an optimum range between 20 and 30 0 C. Elevated temperatures affect nodule initiation and development in temperate legumes, whereas, in tropical legumes it is mainly N 2 fixation efficiency that is affected (Somasegaran et al., 1984). Temperature changes affect the competitive ability of Rhizobium strains and there are also specific temperature-sensitive Rhizobium legume combinations e.g. R. Legumino- sarum biovar-trifolii that forms nodules with Trifolium subterranium (Lewis-Henderson and Djordjevic, 1991(.